Brain virome dysbiosis in Parkinson’s disease and multiple system atrophy - Ghorbani, Mahin; Gabarrini, Giorgio; Hajikhezri, Zamaneh (Frontiers in Microbiology, 2025)
Viral elements have been reported in human brain tissue, yet their presence in the putamen—a region critically affected in Parkinson’s disease (PD) and multiple system atrophy (MSA)has not been characterized. We analyzed whole-genome sequencing data from 32 post-mortem putamen samples (PD: n = 10; MSA: n = 10; healthy controls: n = 12) available under NCBI BioProjects PRJNA756274, PRJNA563007, PRJNA321439, PRJNA555211, and PRJNA555099. Using MetaPhlAn4 for virome profiling, LEfSe for biomarker discovery, and Wilcoxon and ROC analyses for validation, we found that neurodegenerative samples exhibited significantly higher virome alpha diversity compared to healthy controls. LEfSe analysis revealed nine viral species enriched in the neurodegenerative group, including Pestivirus A, Pestivirus Giraffe-1, Woolly monkey sarcoma virus, Abelson murine leukemia virus, Murine osteosarcoma virus, Human endogenous retrovirus K, Salmonella virus SP6, Taterapox virus, and Saccharomyces cerevisiae killer virus M1 (LDA score >2; p < 0.05). In contrast, Alcelaphine gammaherpesvirus 1 was more abundant in controls. While the functional roles of these viruses in the brain remain to be established, several have been previously linked to immunomodulatory effects, suggesting possible relevance to neurodegenerative disease processes. This pilot study provides the first evidence of a brain virome in the human putamen and suggests a potential link between virome dysbiosis and neurodegenerative disease. Distinct viral signatures identified in PD and MSA may serve as candidate biomarkers for early detection and diagnosis.